2014
DOI: 10.1080/02671522.2014.908408
|View full text |Cite
|
Sign up to set email alerts
|

The school’s role in youths’ political efficacy: can school provide a compensatory boost to students’ political efficacy?

Abstract: In the democracies of today, school often have a dual role to play. Not only should they give students the knowledge they need to enter the labour market, they should also teach young people about democracy, and develop students' capacity to exercise their citizenship. A third task for schools is to enhance political equality in society by supporting the least privileged students. In this study, we explore how school can contribute to increased equality by strengthening students' political efficacy. Upper seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
2
26
0
1
Order By: Relevance
“…In the studies by Krampen (1990Krampen ( , 1998, self-concept of one's own political competence was found to be a stable construct which did not show any mean level changes across adolescent years (i.e., ages 14 to 17). Given that other studies showed increasing mean levels for constructs of individual political socialization including efficacy beliefs related to the performance of specific politicsrelated actions (Eckstein et al, 2012;Kerestes et al, 2004;Sohl & Arensmeier, 2015;Zaff et al, 2011), these findings of stability across adolescence are surprising. Instead, students' political efficacy or self-concept of one's own general political competence would have been expected to increase across adolescent years.…”
Section: Development Of Political Efficacymentioning
confidence: 90%
“…In the studies by Krampen (1990Krampen ( , 1998, self-concept of one's own political competence was found to be a stable construct which did not show any mean level changes across adolescent years (i.e., ages 14 to 17). Given that other studies showed increasing mean levels for constructs of individual political socialization including efficacy beliefs related to the performance of specific politicsrelated actions (Eckstein et al, 2012;Kerestes et al, 2004;Sohl & Arensmeier, 2015;Zaff et al, 2011), these findings of stability across adolescence are surprising. Instead, students' political efficacy or self-concept of one's own general political competence would have been expected to increase across adolescent years.…”
Section: Development Of Political Efficacymentioning
confidence: 90%
“…Hoskins et al, 2012;Sohl & Arensmeier, 2015), we should strengthen further the bottom-up perspective on politics, focusing on the (extended) public sphere as a central arena for participation. This focus includes empowering students through participation in discussions, practice in facing opposition and critically reviewing arguments and political information in social media (Journell et al, 2015), including rhetoric with emotional appeal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that discussing politics and social issues in the classroom is strongly associated with students' interest in politics and political efficacy (Kahne et al, 2013;Sohl & Arensmeier, 2015). Teachers play a significant role in supporting and challenging students in such discussions, to facilitate learning experiences where student voices take the lead (Leighton, 2012;Freire, 2014).…”
Section: Engagement Passivity and Detachment: Students' Perspectivesmentioning
confidence: 99%
“…Scales measuring local and school PSE (i.e. internal political efficacy) were constructed based on general guidelines for creating self-efficacy scales (Bandura, 2006) and more general political self-efficacy measures Sohl & Arensmeier, 2015). Using four items, participants assessed their belief that they could carry out four local political activities: organizing a local demonstration; organizing a petition; negotiating with local politicians; and leading a group that stands up for some local cause (e.g., "If I wanted, I think I would be able to negotiate with local politicians").…”
Section: Methodsmentioning
confidence: 99%
“…Although this dimension of classroom climate typically has not been considered in studies of political self-efficacy (Sohl & Arensmeier, 2015 being an exception), peers play a crucial role in adolescents' development (Brown, 2004). More specifically, relationships with classmates can affect adolescents' self-efficacy beliefs.…”
Section: Development Of Political Self-efficacymentioning
confidence: 99%